Investigating the impact of the shadow economy on tax revenue performance in Zimbabwe (1980-2015) - Peter, Lawrence (Midlands State University, 2017)
Despite the tax reforms that have been implemented in Zimbabwe over the years, tax revenue collections have failed to reach sustainable levels that promote growth, development, improve standards of living and most importantly ease the persistent budget deficit problem. One of the major potential threats to tax revenue performance is the shadow economy; it plays a significant role in deteriorating the tax base and this often diminishes tax potential. This motivated an analysis on the potential impact of the shadow economy on tax revenue performance, with the aim of coming up with policy recommendations that will revive the tax performance, help ease the budget deficit problem and boost economic performance. Using annual time series data stretching from 1980 to 2015 and OLS regression, the study examined the impact of the shadow economy on tax revenue performance with a model that included other determinants of tax revenue such as foreign direct investment, government consumption, inflation, real interest rate, agricultural sector share of GDP and manufacturing sector share of GDP. The research results revealed that the shadow economy has a positive significant impact on tax revenue and also indicated that foreign direct investment, government consumption, real interest rate and inflation are compellingly significant in determining tax revenue performance. The study recommend the need to formulate policies that are aimed at enhancing the tax administrative capacity, enforcing voluntary compliance and supporting the informal sector through infrastructure development since it contributes to the well-being of the economy.